The emerging role of extracellular vesicles in viral transmission and immune evasion - Saleem, Muhammad; Chang, Chieh-Wei; Qadeer, Abdul; Asiri, Mohammed; Alzahrani, Fuad M.; Alzahrani, Khalid J.; Alsharif, Khalaf F.; Chen, Chien-Chin; Hussain, Shahid (Frontiers in Immunology, 2025)
Extracellular vesicles (EVs) are membrane-bound structures that serve as major mediators of intercellular communication, playing a crucial role in various physiological and pathological processes. These membrane-bound vesicles are involved in several biological processes and are essential because they play a vital role in regulating viral infections. Given the global burden of viral diseases, understanding the interaction between EVs and viruses is crucial for the development of novel diagnostic tools and therapeutic strategies. This review provides a comprehensive examination of the structure and nature of EVs, as well as their biogenesis and molecular components, distinguishing between exosomes, microvesicles, and apoptotic bodies. We discuss the relationship between EVs and viral diseases, as well as their roles in viral pathogenesis and the dissemination of infections. Moreover, based on the ability of viruses to modulate host immune responses at both the innate and adaptive levels, the involvement of EVs in immune evasion is described. Additionally, the ability of EVs to diagnose viral illnesses and their therapeutic applications, such as using EVs for vaccines, immunotherapy, and the delivery of antiviral drugs, will also be discussed. Various viral diseases, including HIV, hepatitis B and C, and influenza, as well as emerging viruses such as SARS-CoV-2, are reviewed to capture the multifaceted functions of EVs in viral diseases. Finally, the review discusses the limitations of EV research, factors that affect the standardization of the technique, and the outlook for clinical applications. Based on a synthesis of current literature knowledge, this review aimed to identify and highlight the potential of EVs as diagnostic and therapeutic agents in the prevention and treatment of viral infections, thereby paving the way for further research and innovation.